Does early reading instruction promote the rate of acquisition? A comparison of two transparent orthographies. (August 2015) - Soodla, Piret; Lerkkanen, Marja-Kristiina; Niemi, Pekka; Kikas, Eve; Silinskas, Gintautas; Nurmi, Jari-Erik
Abstract: This study examines the development of children's reading skills in two transparent orthographies, Estonian and Finnish. Formal reading instruction begins one year earlier in Estonia than in Finland; thus, it was expected that Estonian children would outperform their Finnish peers in reading achievement during grade 1. In this study, 433 Estonian and 353 Finnish first graders were assessed for letter knowledge, phoneme awareness, and reading accuracy and fluency at the beginning of first grade while reading fluency and reading comprehension were assessed in the final semester of first grade. The results showed that, despite Estonian children's better reading skills at the beginning of the school, fluency and reading comprehension skills were at the same level across both groups by the end of first grade. This finding indicates that early reading instruction in transparent orthographies does not necessarily give any long-term advantage for further success in reading development at school. Highlights: The Estonian and Finnish languages have highly transparent orthographies. In Estonia, formal reading instruction begins one year earlier than in Finland. Estonian children outperform their Finnish peers in decoding at school entrance. By the end of Grade 1, children's reading skills were at similar level.